Creation lake : a novel - Kushner, Rachel (Scribner, 2024)
"Creation Lake is a novel about a freelance agent, a 34-year-old American woman of ruthless tactics and bold opinions and clean beauty, who is sent to do dirty work in France. "Sadie Smith" is how the narrator introduces herself to her lover, to the rural commune of French subversives on whom she is keeping tabs, and to the reader. We never learn her real name. Sadie has met her lover, Lucien, a young and well-born Parisian, by "cold bump"- making him believe the encounter was accidental. And like everyone she chooses to interact with, Lucien is useful to her, used by her. Sadie operates on strategy and dissimulation, based on what her "contacts," shadowy figures in business and government, instruct. First, these contacts want her to incite provocation. Then they want more. In this region of centuries-old farms and ancient caves, Sadie becomes entranced by a mysterious figure named Bruno Lacombe, a mentor to the young activists, who lives in a vast network of underground caves on his daughter's land and communicates only by email. Bruno believes that the path to emancipation from what ails modern life is not revolt, but a return to the ancient past before civilization. Just as Sadie is certain she's the seductress and puppet master of those whom she surveils, Bruno Lacombe is seducing her with his ingenious counter-histories, his artful laments, his own tragic story. Written in short, vaulting sections, Rachel Kushner's rendition of "noir" is taut, propulsive, and dazzling. Creation Lake is Kushner's finest achievement yet as a novelist, a work of high art, high comedy, keen insights, and unforgettable pleasure. From Rachel Kushner on the title: My character Bruno refers to "a deep cistern of voices, the lake of our creation" - meaning all of human history, the whole struggle in which chains of civilizations try to figure out how to live. He believes he can hear these voices underground. To me, "Creation Lake" suggests intrigue. Creation of what? In Sadie's case, a persona, a feint, a manipulation. But also in her case, the creation possibly of her own soul"--